2016
DOI: 10.3324/haematol.2016.148908
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in long-term survivors of childhood acute leukemia treated without hematopoietic stem cell transplantation: an L.E.A. study

Abstract: C ardiovascular conditions are serious long-term complications of childhood acute leukemia. However, few studies have investigated the risk of metabolic syndrome, a known predictor of cardiovascular disease, in patients treated without hematopoietic stem cell transplantation. We describe the overall and age-specific prevalence, and the risk factors for metabolic syndrome and its components in the L.E.A. (Leucémie de l'Enfant et de l'Adolescent) French cohort of childhood acute leukemia survivors treated withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 52 publications
3
24
1
Order By: Relevance
“…2,4,7,25,26 Children after therapy of ALL are also at substantial risk of cardiovascular disease development in adulthood. 15,16,27 It was also confirmed that cancer childhood survivors are approx. 8 times more likely to die due to cardiac-related events as compared to the general population.…”
Section: Discussionmentioning
confidence: 74%
“…2,4,7,25,26 Children after therapy of ALL are also at substantial risk of cardiovascular disease development in adulthood. 15,16,27 It was also confirmed that cancer childhood survivors are approx. 8 times more likely to die due to cardiac-related events as compared to the general population.…”
Section: Discussionmentioning
confidence: 74%
“…The risk of developing metabolic syndrome was even higher among patients who received CNS irradiation (OR: 2.32, 95%CI: 1.36–3.97; P =0.002), which confirms the results of previous studies. 15 , 17 , 38 Interestingly, those patients had a much larger waist circumference compared with the IPC group. This highlights the impact of CNS irradiation on the development of obesity, an observation which has been previously described 11 , 41 , 42 and debated.…”
Section: Discussionmentioning
confidence: 90%
“… 50 Therefore, TBI exposure may induce adipose tissue abnormalities, as suggested by animal models, 51 and contribute to the development of metabolic syndrome. Our previous studies indicated that high-dose corticosteroids do not have an impact on metabolic syndrome, 11 , 15 and, therefore, this hypothesis remains controversial. 11 , 15 …”
Section: Discussionmentioning
confidence: 97%
“…Poor diet and a sedentary lifestyle could further increase these already elevated risks. Personal counseling should be offered to childhood cancer patients and their parents throughout treatment and beyond, and special attention should be given to patients with an increased BMI (48). However, counseling during this period, when patients and families face the crisis of a life-threatening illness and nutritional status is not a first priority, is challenging.…”
Section: Implications and Recommendationsmentioning
confidence: 99%